Digital-based gymnastics learning media for rolling front round material: Direct and indirect assistance approaches - Zulbahri; Sepriadi; Mario, Deby Tri; Astuti, Yuni; Amra, Frizki (Journal Sport Area, 2022)
Digital-based gymnastics learning media is one of the efforts to achieve effective and efficient learning goals, especially in the rolling front round material. Therefore, this study aims to develop digital-based gymnastics learning media on rolling front round material which contains a direct assistance approach and indirect assistance approach. This research is a research and development that aims to produce and test the effectiveness of the product. This research consists of several stages, namely product design, product testing, and product implementation. A total of 45 gymnastics students at the department of sports education, faculty of sports science, Padang State University were used as research samples. 15 of them were used for small group trials, and 30 for large group trials. This research also involves material experts and media experts to validate the products developed. Expert validation results obtained an average of 83.33 or very good (material experts 80.00 and media experts 86.67). Meanwhile, the results of field trials obtained an average of 88.06 or showed a very high level of reliability (small group 88.90 and large group 87.23). In conclusion, this developed media can be used as a tool in learning gymnastics, whether it is used for physical education teachers, students, and athletes to improve round front rolling skills. Future research is needed to involve other materials in gymnastics learning with an attractive design and appearance, as well as a wider sample size.